The Usage of Digital Technology in Teaching Biology (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article provides information about the methods and possibilities of using digital technologies in the teaching of biological science. The programs that can be used in biological science and the effects of these programs on the effectiveness of the lesson are widely covered.